Benchmark Analysis of Numerical Models for Tsunami Simulation - IAEA (IAEA-TECDOC., 2022)
In recent years there has been an evolution in numerical models used to compute tsunami propagation and run-up. Many models currently available offer a wide array of choices to the users. In parallel with the development of such numerical models, it is important that the user only applies the verified and validated numerical models that have undergone a benchmark analysis. This publication provides information and benchmark problems to enable engineers and regulators to select the most appropriate tsunami analysis software and modelling for the evaluation of tsunami hazards for nuclear installations to ensure their safety against those events. In addition, the benchmark problems will enable such users to become familiar with the limitations of the tsunami analysis modelling available in research and commercial software.